Investigation and performance analysis of Nanoscale communication network for biomedical application - Liza, Farhana Ahmed; Hasan, Mahmudul; Islam, Nusrat; Paul, Tanmoy (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.